Thermal and arc erosion behavior of CuCr contact material based on large plastic deformation treatment - Xiuhua Guo; Kaiyue Duan; Xu Wang; Kexing Song; Xiangfeng Zhang; Kai Li (Journal of Materials Research and Technology, 2023)
CuCr alloys are the main contact materials used in medium-voltage and high-current vacuum interrupters. In this paper, the effect of large plastic deformation on microstructure and the transverse/longitudinal thermal conductivity of CuCr30 contact material were studied. The results show that the morphology of Cr particles in CuCr30 changes from dendritic to oriented fibrous after large plastic deformation, and the longitudinal thermal conductivity of CuCr30 contact material is about 1.5 times higher than its transverse thermal conductivity. During the electrical contacting process, the mass loss of the extruded CuCr30 contact material is lower than that of as-cast CuCr30 contact material, which is directly related to the significantly higher longitudinal thermal conductivity of the extruded CuCr30 contact material. The enhancement of longitudinal thermal conductivity is beneficial to reduce the mass loss of the contact material and improve the arc erosion resistance of the contact material. The mass loss of the cathode with higher longitudinal thermal conductivity is significantly lower than that of the anode contact in extruded CuCr30 contact material.